The value of tours around heritage sites with Melville Koppies as an example (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Tours enrich and reinforce textbook and classroom history, inspire further study, and promote an appreciation of past cultures. This paper discusses the value of guided tours on Melville Koppies, a Nature Reserve and Johannesburg Heritage Site. Melville Koppies offers evidence of man-made structures and artefacts reflecting Pre-History from Early Stone Age to Iron Age in this undeveloped pristine reserve where the natural sciences and social sciences meet. The site includes evidence of gold mining attempts, the Second Anglo-Boer War and modern history up to present times. The panoramic view from the top ridges of the Koppies encompasses places of rich historical interest, of which many, such as Sophiatown and Northcliff Ridge, were affected by apartheid. Guided tours are tailored to educators’ requirements and the age of students. These educators usually set their own pre- or post-tour tasks. The logistical challenges for educators of organising such three-hour tours are discussed. History, if part of a life-time awareness, is not confined to primary, secondary or tertiary learners. Further education for visitors of all ages on guided tours is also discussed.
Keywords: Wealth of evidence; Social and natural sciences meet; Guided tours; Enrichment